Outdoor time, screen time and sleep reported across early childhood: concurrent trajectories and maternal predictors - Katherine L. Downing; Borja del Pozo Cruz; Taren Sanders; Miaobing Zheng; Jill A. Hnatiuk; Jo Salmon; Kylie D. Hesketh (BMC, 2022)
Abstract Background Understanding the developmental trajectories of outdoor time, screen time and sleep is necessary to inform early interventions that promote healthy behaviours. This study aimed to describe concurrent trajectories of outdoor time, screen time and sleep across the early childhood period and their maternal predictors. Methods Data across five time points at child age 4, 9, 19, 42 and 60 months from the INFANT intervention were analysed. Mothers reported their child's usual outdoor time, screen time and sleep duration, in addition to a range of maternal beliefs, attitudes, expectations and behaviours. Group-based multi-trajectory modelling was used to model concurrent trajectories of children's behaviours. Multinomial logistic regression models determined the associations of maternal predictors with trajectory groups, adjusting for child sex and baseline age, intervention allocation, and clustering by recruitment. Results Of the 542 children recruited, 528 had data for outdoor time, screen time and sleep at one or more time points and were included in trajectory analyses Four trajectories were identified: 'unstable sleep, increasing outdoor time, low screen' (~ 22% of sample), 'high outdoor time, low screen, high sleep' (~ 24%), 'high sleep, increasing outdoor time, low screen' (~ 45%), 'high screen, increasing outdoor time, high sleep' (~ 10%). The 'high sleep, increasing outdoor time, low screen' group, comprising the largest percentage of the sample, demonstrated the healthiest behaviours. Predictors of group membership included: views of physically active children, screen time knowledge, screen time use, self-efficacy, physical activity optimism, future expectations for children's physical activity and screen time, perceptions of floor play safety, and maternal physical activity, screen time, and sleep quality. Conclusions Four distinct trajectories of outdoor time, screen time and sleep were identified, with the most common (and healthiest) characterized by high levels of sleep. Maternal beliefs, attitudes, expectations and behaviours are important in the development of movement behaviour trajectories across early childhood. Future interventions and public policy may benefit from targeting these factors to support healthy movement behaviours from a young age.